TDP-43 regulates site-specific 2′-O-methylation of U1 and U2 snRNAs via controlling the Cajal body localization of a subset of C/D scaRNAs. Issue 5 (13th February 2019) - Izumikawa, Keiichi; Nobe, Yuko; Ishikawa, Hideaki; Yamauchi, Yoshio; Taoka, Masato; Sato, Ko; Nakayama, Hiroshi; Simpson, Richard J; Isobe, Toshiaki; Takahashi, Nobuhiro
Abstract: TDP-43 regulates cellular levels of Cajal bodies (CBs) that provide platforms for the assembly and RNA modifications of small nuclear ribonucleoproteins (snRNPs) involved in pre-mRNA splicing. Alterations in these snRNPs may be linked to pathogenesis of amyotrophic lateral sclerosis. However, specific roles for TDP-43 in CBs remain unknown. Here, we demonstrate that TDP-43 regulates the CB localization of four UG-rich motif-bearing C/D-box-containing small Cajal body-specific RNAs (C/D scaRNAs; i.e. scaRNA2, 7, 9 and 28) through the direct binding to these scaRNAs. TDP-43 enhances binding of a CB-localizing protein, WD40-repeat protein 79 (WDR79), to a subpopulation of scaRNA2 and scaRNA28; the remaining population of the four C/D scaRNAs was localized to CB-like structures even with WDR79 depletion. Depletion of TDP-43, in contrast, shifted the localization of these C/D scaRNAs, mainly into the nucleolus, as well as destabilizing scaRNA2, and reduced the site-specific 2′- O -methylation of U1 and U2 snRNAs, including at 70A in U1 snRNA and, 19G, 25G, 47U and 61C in U2 snRNA. Collectively, we suggest that TDP-43 and WDR79 have separate roles in determining CB localization of subsets of C/D and H/ACA scaRNAs.